The Ability of Different Nickel-Titanium Rotary Instruments To Induce Dentinal Damage During Canal Preparation - Souza Bier, Carlos Alexandre [UNESP]; Shemesh, Hagay; Tanomaru-Filho, Mario [UNESP]; Wesselink, Paul R.; Wu, Min-Kai (Elsevier B.V., 2009)
The purpose of this study was to compare the incidence of dentinal defects (fractures and craze lines) after canal preparation with different nickel-titanium rotary files. Two hundred sixty mandibular premolars were selected. Forty teeth were left unprepared (n = 40). The other teeth were prepared either with manual Flexofiles (n = 20) or with different rotary files systems: ProTaper (Dentsply-Maillefer, Ballaigues, Switzerland), ProFile (Dentsply-Maillefer), SystemGT (Dentsply-Maillefer), or S-ApeX (FKG Dentaire, La Chaux-de-Fonds, Switzerland) (n = 50 each). Roots were then sectioned 3, 6, and 9 mm from the apex and observed under a microscope. The presence of dentinal defects was noted. There was a significant difference in the appearance of defects between the groups (p < 0.05). No defects were found in the unprepared roots and those prepared with hand files and S-ApeX. ProTaper, ProFile, and GT preparations resulted in dentinal defects in 16%, 8%, and 4% of teeth, respectively. Some endodontic preparation methods might damage the root and induce dentinal defects. (J Endod 2009;35:236-238)
Keywords: Craze lines; dentinal defects; nickel-titanium instruments; root canal preparation